A 5 year retrospective analysis of common intestinal parasites at Poly Health Center, Gondar, Northwest Ethiopia - Ayelgn, Meseret (BMC Res Notes, 2019)
OBJECTIVE: Intestinal parasites are present throughout the world in varying degrees of prevalence due to many factors. The aim of this study was to determine the 5-year trend prevalence of intestinal prevalence among patients who had been suspected for intestinal parasite infections. A retrospective study was conducted from 2009 to 2013 at Poly Health Center Gondar, Northwest Ethiopia. Samples were examined using direct saline wet mount methods. Statistical analysis was done using SPSS version 20 software and a P-value of < 0.05 was considered statistically significant. The results were presented in tables and graphs. RESULTS: During the study period, a total of 13,329 stool samples were requested for intestinal parasite diagnose and 5510 (41.3%) laboratory-confirmed cases were reported with a fluctuating trend. Ten different parasites were reported in each year with Entamoeba histolytica/dispar (16.8%) being the predominant parasite followed by Giardia lamblia (11.4%) and Ascaris lumbricoides (6.7%). Both males (49%) and females (51%) were equally affected (P = 0.14). The intestinal parasite was reported in all age groups in the area but the highest and the lowest prevalence were reported in age groups of 20–29 years and 40–49 years, respectively (26.5% vs 6.4%) (P < 0.001).